KONTRIBUSI PEGADAIAN SYARIAH UNTUK MENUNJANG PEREKONOMIAN MASYARAKAT DI INDONESIA - RACHMAWATI, NINDA; ANANTA UPA, VIERLY (STIEKOP MALANG PRESS, 2025)
Purpose – Pegadaian Syariah, or Islamic Pawnshops, contribute to Indonesia's economic landscape by providing accessible financial solutions aligned with Islamic principles. They offer crucial microfinancing alternatives, enabling individuals and small businesses, often excluded from traditional banking, to access capital for immediate needs and entrepreneurial endeavors. This, in turn, stimulates economic activity at the grassroots level and fosters financial inclusion within Indonesian communities. Design/methodology/approach – This study employs a qualitative approach, analyzing the contributions of Sharia pawnshops (